2020
DOI: 10.1177/0300060519897195
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant-prosthetic dental rehabilitation of patients with diabetes using four immediately loaded dental implants: a pilot study

Abstract: Objectives: Type 2 diabetes mellitus (T2DM) involves endocrine changes that cause a persistent increase in blood glucose. Many disorders are associated with T2DM, including disorders that affect the oral cavity. Oral cavity disorders interfere with a patient's capacity to follow a correct diet, which results in worsening systemic disease. Oral rehabilitation is necessary for patients with T2DM. Therefore, this prospective study was performed to evaluate the immediate dental rehabilitation capacity of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The countries in which the 7 included studies were conducted were Portugal, Lebanon, Spain, Saudi Arabia, Egypt, and Romania [ 16 , 17 , 19 , 20 , 24 , 26 , 27 ]. All the studies were published in the English language between 2008 [ 24 ] and 2020 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The countries in which the 7 included studies were conducted were Portugal, Lebanon, Spain, Saudi Arabia, Egypt, and Romania [ 16 , 17 , 19 , 20 , 24 , 26 , 27 ]. All the studies were published in the English language between 2008 [ 24 ] and 2020 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The countries in which the 7 included studies were conducted were Portugal, Lebanon, Spain, Saudi Arabia, Egypt, and Romania [ 16 , 17 , 19 , 20 , 24 , 26 , 27 ]. All the studies were published in the English language between 2008 [ 24 ] and 2020 [ 26 ]. Five studies were longitudinally observational [ 16 , 19 , 24 , 26 , 27 ], and two studies were clinical trials [ 17 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been success demonstrated in immediate implantation and prosthetic rehabilitation employing the All-in-Four method, when working with patients with type 2 diabetes. In R.I. Juncar's study, implants demonstrated good osseointegration and stability 6 months after the installation in individuals with diabetes; however, the authors emphasize the importance of maintaining proper oral hygiene and glycemic control for better postoperative recovery [36].…”
Section: E N T I S T R Ymentioning
confidence: 98%